Interactive Data Quality Dashboard: Integrating Real-Time Monitoring with Predictive Analytics for Proactive Data Management - Gami, Sandip J; Shah, Kevin; Katru, Chandrasekhar Rao; Nagarajan, Sevinthi Kali Sankar (International Journal of Computer Sciences and Engineering, 2024)
The "Interactive Data Quality Dashboard" integrates real-time monitoring with predictive analytics to enhance proactive data management and support high standards of data governance. In response to the exponential growth in data generation across modern organizations, this dashboard provides a critical solution for maintaining data quality, integrity, and consistency. Leveraging predictive analytics, the system forecasts potential data quality challenges, allowing users to address issues before they escalate. By enabling early detection of data inconsistencies, this platform fosters a preventative approach to data management that significantly reduces risks associated with data discrepancies. Designed with user-friendliness in mind, the dashboard provides intuitive interfaces and real-time feedback mechanisms that simplify the visualization, assessment, and management of data quality. Users are equipped with actionable insights that support continuous improvement in data accuracy, completeness, and consistency across various data environments. Additionally, the automation of data validation processes minimizes manual effort, streamlining workflows and increasing operational efficiency. This proactive approach not only enhances decision-making capabilities but also supports strategic data-driven initiatives within organizations. By continuously analyzing and visualizing real-time data quality metrics, the dashboard ensures that data remains reliable and ready for effective use. The integration of predictive algorithms allows organizations to adapt to emerging trends and address future data challenges, fostering resilience and adaptability in data management practices. For organizations aiming to uphold high standards in data governance and quality control, the Interactive Data Quality Dashboard offers a powerful tool that combines advanced analytics with real-time monitoring to drive sustainable data quality management.